Waqf Information System (Siwak) and Problems of Its Application: The Case on Kantor Urusan Agama Sui Raya, Kubu Raya, West Kalimantan - Hakim, Muhammad Lutfi (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2020)
The data collection of waqf land on SIWAK application is one form of information disclosures to the public and information exchange in government agencies to realize good governance. Unfortunately, the utilization of the SIWAK application was not carried out optimally by the KUA in Sui Raya Sub-District. This paper aims to describe and analyze the implementations and procedures for data collection of waqf land through the SIWAK application and the constraints found in the KUA in Sui Raya Sub-District. Using empirical research and the case study approach, there are three research results in this paper. First, the data collection program of waqf land on KUA Sui Raya Sub-District is divided into two: the data collection of waqf land manually and online through the SIWAK application. Second, the procedure for data collection of waqf land through the SIWAK application is the same as the procedure for manual registration of waqf land. After the pledge of waqf was pledged by wÄkif to nÄdzir in the presence of PPAIW and two witnesses, the data was then submitted by Functional Penghulu into the SIWAK application. Third, there are two constraints experienced by the Functional Penghulu in KUA Sui Raya Sub-District in collecting data on waqf land through the SIWAK application, namely the lack of human resources and the lack of available facilities,no internet network to access the SIWAK application. The author argues that the democratization of sharia carried out by the government regarding the data collection of waqf assets must be able to overcome existing obstacles to provide legal certainty and justice for Muslim communities in Indonesia in waqf.